Is laparoscopic experience helpful in simulator based robotic training in general surgery? - Shahriyar Ghazanfar; Sajida Qureshi; Muhammad Zubair; Yumnah Safdar; Aftab Ahmed Leghari; Mohammad Saeed Quraishy (Journal of the Pakistan Medical Association, 2021)
Objective: To evaluate whether or not prior laparoscopic training improves performance during robotic surgery utilising DaVinci robotic skills simulator. Methods: The cross-sectional study was conducted at the Civil Hospital, Karachi, from May 4 to November 11, 2018, and comprised first year residents in Group A with no laparoscopic skills and fourth year residents doing laparoscopic cholecystectomy independently and surgical faculty members in Group B who had laparoscopic skills. Both the groups had no previous exposure to robotic surgery and skills simulator. There were 4 exercises which were repeated three times by each participant. Scoring was done using the the DaVinci robotic skills simulator software. Data was analysed using SPSS 22. Results: Of the 30 surgeons, there were 15(50%) in Group A with a mean age of 26±0.56 years, and 15(50%) in Group B with a mean age of 32 years± 9.16 (p<0.001). The overall mean age was 32±9.16 years (range: 25-52 years). There were 19(63.3) females in the sample compared to 11(36.6%) males. Mean scores of Ring walk 2, Peg board 2, and Suture sponge 3 were better in Group A, while mean score of Matchboard 2 was better in Group although B (p>0.05). Group B fared better in the individual scoring of Suture sponge 2 (p>0.05). Conclusion: Laparoscopic skills apparently did not confer any benefit while performing exercises on the DaVinci skills simulator. Key Words: DaVinci Si, DaVinci skills simulator, dVSSS, Robotic surgery curriculum, Robotic surgery simulation. Continuous...